Teaching restorative justice - Pointer, Lindsey (Contemporary justice review, 2022)
This article outlines four pillars of restorative pedagogy, drawing on relevant literature as well as collective learning distilled through a reflective circle process held by the authors during a course called Teaching Restorative Justice at Vermont Law and Graduate School. The four pillars are (1) prioritizing relationships, (2) practicing self-reflection, (3) cultivating dialogue that unearths social systems of oppression, and (4) utilizing strategies for creative and experiential engagement. These four pillars generate a space that promotes a deep integration of class material and activates the community toward social change. The authors reflect on their experience sharing a classroom community as students and professor and on the impact of these pillars on cultivating education as a practice of freedom.